Institutional Imbalance, Marketized Mentality, and the Justification of Instrumental Offenses: A Cross-National Application of Institutional Anomie Theory. (16th April 2021) - Hövermann, Andreas; Messner, Steven F.
Abstract: The present study builds upon prior research that has suggested that the social psychological concept of "marketized mentality" (MM) can serve as a conceptual lynchpin to facilitate multilevel analyses informed by Institutional Anomie Theory (IAT), a macro-sociological theory of crime. We examine the connection between a societal indicator of institutional imbalance – a key IAT concept – and a measure of the prevalence of MM with a much larger sample of nations than analyzed previously (58 countries). In addition, we broaden the domain of "outcomes" related to MM to include an attitudinal variable relevant to crime – the willingness to justify instrumental offenses. Consistent with theoretical expectations, the results reveal significant relations between MM, the degree of institutional imbalance, and the willingness to justify instrumental offenses. These findings indicate the potential promise of developing an integrated, micro-macro approach to understanding criminological phenomena by incorporating MM within the IAT-analytic framework.